Widespread Expression of Hedgehog Pathway Components in a Large Panel of Human Tumor Cells and Inhibition of Tumor Growth by GANT61: Implications for Cancer Therapy - Réda, Jiri; Vachtenheim, Jiri; Vlčková, Kateřina; Horák, Pavel; Vachtenheim, Jiri; Ondrušová, Lubica (International journal of molecular sciences, 2018)
The sonic Hedgehog/GLI signaling pathway (HH) is critical for maintaining tissue polarity in development and contributes to tumor stemness. Transcription factors GLI1⁻3 are the downstream effectors of HH and activate oncogenic targets. To explore the completeness of the expression of HH components in tumor cells, we performed a screen for all HH proteins in a wide spectrum of 56 tumor cell lines of various origin using Western blot analysis. Generally, all HH proteins were expressed. Important factors GLI1 and GLI2 were always expressed, only exceptionally one of them was lowered, suggesting the functionality of HH in all tumors tested. We determined the effect of a GLI inhibitor GANT61 on proliferation in 16 chosen cell lines. More than half of tumor cells were sensitive to GANT61 to various extents. GANT61 killed the sensitive cells through apoptosis. The inhibition of reporter activity containing 12xGLI consensus sites by GANT61 and cyclopamine roughly correlated with cell proliferation influenced by GANT61. Our results recognize the sensitivity of tumor cell types to GANT61 in cell culture and support a critical role for GLI factors in tumor progression through restraining apoptosis. The use of GANT61 in combined targeted therapy of sensitive tumors, such as melanomas, seems to be immensely helpful.
Keywords: jaderné proteiny; nádorové buněčné linie; signální transdukce; Zinc Finger Protein GLI1; Disease Progression; Jurkat buňky; Hedgehog Proteins; Nuclear Proteins; progrese nemoci; regulace genové exprese u nádorů; proteiny hedgehog; HeLa Cells; Pyridines; Signal Transduction; pyridiny; Cell Proliferation; Cell Line, Tumor; Pyrimidines; pyrimidiny; tumor cell lines; Neoplasms; protein Gli2 s motivem zinkových prstů; Humans; Gene Expression Regulation, Neoplastic; nádory; Hedgehog; Jurkat Cells; viabilita buněk; Cell Survival; GLI; proliferace buněk; Zinc Finger Protein Gli2; GANT61; protein Gli1; apoptosis; HeLa buňky; lidé